Influence of Extrusion of White Lupins (Lupinus albus L.) on the Apparent Metabolizable Energy and Ileal Nutrient Digestibility for Broilers - Son, Jang-Ho.; Ravindran , Velmurugu (International Journal of Poultry Science, 2012)
In the present study, the influence of extrusion on the composition and nutritive value of white lupins (Lupinus albus L.) was evaluated. The extrudate was produced by the extrusion cooking of white lupins at 22% moisture level and 140°C. Three treatment diets consisting of a corn-soy basal diet and two test diets containing raw and extruded lupin meals were formulated and, assayed in digestibility and balance trials using 4-week old broiler chickens. The test diets were formulated by substituting the raw and extruded lupin meals for 25% (w/w) of the basal diet. Apparent ileal nutrient digestibility was calculated using titanium oxide as the indigestible indicator and the Apparent Metabolizable Energy (AME) was determined using the classical total excreta collection method. Extrusion of white lupins had no effect (p<0.05) on the contents of crude protein, crude fat, ash and most amino acids. Soluble Non-Starch Polysaccharide (NSP) contents were increased (p<0.05) and the insoluble NSP contents were lowered (p<0.05) by extrusion. Increased soluble NSP contents were associated with reduced (p<0.05) ileal digestibility of fat and AME. Trypsin inhibitor activity was reduced (p<0.05) following extrusion, but this reduction had no effect (p>0.05) on the ileal digestibility of protein and amino acids. Overall, under the extrusion conditions employed in the present study, extrusion cooking adversely affected the AME but had no effect on the ileal digestibility of protein and amino acids in white lupins for broilers.